DAMPAK PERANG DAGANG AMERIKA SERIKAT-CINA TERHADAP PERTUMBUHAN INVESTASI ASING DI VIETNAM TAHUN 2018-2019 - Vina Benita Laksono; Triesanto Romulo Simanjuntak; Christian H.J De Fretes (Universitas Kristen Satya Wacana, 2020)
The economic tensions that led to the Trade War between the United States and China not only shook and hurt the economies of both the United States and China. Tax returns that continue to heat up and increase between the two countries with the strongest economies in the world are able to weaken global economic growth. In addition to the negative impacts arising from the Trade War, one of the countries in Southeast Asia, Vietnam was able to get a positive impact from the spillover of the Trade War that could increase its economic growth. The purpose of this research is to determine the impact of the United States-China Trade War on the growth of foreign investment in Vietnam in 2018-2019. This research uses a qualitative analysis approach with a descriptive explanative writing method using secondary data sources. The results of this study stated that the growth of foreign investment and trade in Vietnam in 2018-2019 increased significantly because it was influenced by two factors, namely external factors were the spillover of the United States-China Trade War, and internal factors were the internal economic and political conditions of Vietnam which tended to stable because there is Doi Moi or economic reforms carried out by the Vietnamese Government since 1986.